KUALITAS MAKROSKOPIS DAN MIKROSKOPIS MORFOLOGI SEL LEKOSIT PADA SADT BERDASARKAN VARIASI SUHU PENGERINGAN - Budi Santosa; Rina Febriyani (Universitas Respati Yogyakarta, 2020)
Background Clean and Healthy Life Behaviour (PHBS) program is an effort to empower all people at school, particularly student, to have an awareness on being healthy. According to Dinas Kesehatan Provinsi DIY (2012), there are eight indicators of PHBS. The aim of this research is to develop the game as health promotion media for 4th grade student at SDN Ngblak. Objective: to determine the extent to which temperature affects the macroscopic morphology of SADT and the morphological quality of leukocyte cells in SADT preparations. Method: Third level of Research and Development method was used for this research. The research’s subjects were media expert, material expert, and 12 students as they will give review and advice on the ‘ular tangga’ traditional game development. Data analysis used is qualitative. Result: The result of the 2ndvalidity test by the media expert, material expert, and game users for the ‘ular tangga’ traditional game as the health promotion media at elementary schoolwere 86%, 98%, and 90,27%, respectively. Overall, the results were very good. Conclusion:A set of Clean and Healthy Behaviour ‘ular tangga’ traditional game is feasible to be used as helath promotion media for 4th grade elementray school students.